تقنيات الذكاء الاصطناعي في برامج المكتبات والمعلومات: دراسة تحليلية - محمد، أسماء سيد (جامعة الأزهر - كلية الدراسات الإنسانية, 2022)
تهدف الدراسة إلى تحليل محتوى المقررات الدراسية في عينة عمدية من مدارس وأقسام المكتبات والمعلومات الأجنبية والعربية؛ للتعرف على واقع تدريس الذكاء الاصطناعي بأقسام المكتبات والمعلومات على المستويين الأجنبي والعربي باستخدام المنهج الوصفي التحليلي؛ للخروج بمؤشرات يمكن أن تساهم في وضع توصيف خاص بموضوع الذكاء الاصطناعي وتطبيقاته بأقسام المكتبات والمعلومات بالجامعات المصرية، وقد توصلت الدراسة إلى العديد من النتائج من أهمها بلغ إجمالي المقررات الدراسية في أقسام المكتبات والمعلومات بالجامعات العربية والأجنبية للعام الجامعي 2021/2022م (١٢٢) مقررًا؛ كما تبين أن جميع أقسام المكتبات والمعلومات بالجامعات الأمريكية عينة الدراسة، والبالغ عددها (١٠) أقسام يتوافر بها مقررات عن الذكاء الاصطناعي بواقع (١١٨) مقررًا بنسبة (96,7%)، وأن أقسام المكتبات والمعلومات بالجامعات العربية لا يوجد بها إلا أربعة مقررات فقط عن الذكاء الاصطناعي والمتاحة في قسم المعلومات بجامعة الملك عبد العزيز وجامعة الملك سعود، وجامعة القاهرة بنسبة (3,3%)؛ كما بلغت عدد المقررات الإجبارية في مجال الذكاء الاصطناعي (٢٩) مقررًا بنسبة بلغت 23,8%، والمقررات الاختيارية في مجال الذكاء الاصطناعي (٩٣) مقررًا بنسبة بلغت 76,1%؛ كما تبين ظهور مصطلح الذكاء الاصطناعي في مسميات (٣٦) مقررًا في جميع أقسام المكتبات والمعلومات عينة الدراسة بنسبة 100% من إجمالي المقررات الأساسية، وعليه قدمت الدراسة عددًا من التوصيات منها أنه يجب تحديث لوائح أقسام المكتبات والمعلومات لمواكبة سوق العمل، وإضافة بعض المقررات المساعدة لتدريس الذكاء الاصطناعي في أقسام المكتبات والمعلومات، وتخصيص ميزانيات لدعم التطور التكنولوجي وتقنيات الذكاء الاصطناعي. The study aims to analyze the content of the courses in a selected sample of foreign and Arabic schools and departments of libraries and information, To identify the reality of teaching artificial intelligence in library and information departments at the international and Arab levels, by using the descriptive analytical approach; to come up with indicators that can contribute to developing a specific description of the subject of artificial intelligence and its applications in library and information departments in Egyptian universities. Arab and American for 2021/2022 were (122) courses; It was found that all libraries and information departments in American universities were (10) departments, that have courses on artificial intelligence, amounting to (118) courses, at a rate of (96.7%), and that the library and information departments in Arab universities have only four courses on intelligence. artificial intelligence and available in the Information Department of King Abdulaziz University, King Saud University, and Cairo University (3.3%); The number of compulsory courses in the field of artificial intelligence reached (29) with a rate of 23.8%, and elective courses in the field of artificial intelligence (93) with a rate of 76.1%; It was also shown that the term artificial intelligence appeared in the names of (36) courses in all departments of libraries and information, the sample of the study was 100% of the total core courses. The study provided a number of recommendations: The regulations of library and information departments must be updated to keep pace with the labor market, add some courses to teach artificial intelligence in library and information departments, and allocate budgets to support technological development and artificial intelligence techniques.
Keywords: الذكاء الاصطناعي -- تكنولوجيا المعلومات -- المناهج الدراسية -- التنمية التكنولوجية -- مصر